The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9sm01348b
|View full text |Cite
|
Sign up to set email alerts
|

Slide electrification: charging of surfaces by moving water drops

Abstract: We investigate the charge separation caused by the motion of a water drop across a hydrophobic, insulating solid surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
122
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(127 citation statements)
references
References 71 publications
4
122
1
Order By: Relevance
“…Handling of liquid droplets has received great interest in a broad range of research areas including microfluidics, enabling chemical reactions, medical analysis, separation and extraction of target analytes, triboelectric generation, and water harvesting. [ 8,45–50 ] The shape‐designable polyhedral LMs/LPs developed in this study show unique handling abilities and should attain great interest due to possible applications including high‐performance microreaction containers and sensors. [ 51,52 ]…”
Section: Resultsmentioning
confidence: 99%
“…Handling of liquid droplets has received great interest in a broad range of research areas including microfluidics, enabling chemical reactions, medical analysis, separation and extraction of target analytes, triboelectric generation, and water harvesting. [ 8,45–50 ] The shape‐designable polyhedral LMs/LPs developed in this study show unique handling abilities and should attain great interest due to possible applications including high‐performance microreaction containers and sensors. [ 51,52 ]…”
Section: Resultsmentioning
confidence: 99%
“…As reported before, negative charges preferentially adsorbed at hydrophobic surfaces. [33][34][35] Previous observations indicated that fluoropolymer materials even spontaneously and permanently adsorb negative charges upon extended contact with water. [25] The highest charge densities had been reported for elevated pH.…”
mentioning
confidence: 99%
“…In many ENGs, the water drops also fulfill a second role: in addition to providing the required initial mechanical energy, the impact process is also responsible for the generation of the trapped surface charge on the hydrophobic surface [6,9,12]. However, like other triboelectric charging mechanisms that have been explored, this process is notoriously difficult to control and dependent on details of materials and process conditions [16][17][18]. The poor stability of surface charges generated by drop impact, tribocharging, and hydrophobicwater contact [19][20][21][22][23][24] compromises the performance and stability of possible devices and has also hampered the development of a quantitative model of the energy conversion process, which is needed to provide guidelines for further improvements of the technology.…”
mentioning
confidence: 99%